2002
DOI: 10.1046/j.1442-2042.2002.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bladder volume on transabdominal ultrasound measurements of intravesical prostatic protrusion and volume

Abstract: Background : A filled bladder acts as an acoustic window for transabdominal ultrasound measurements of intravesical prostatic protrusion and volume. The aim of this study is to evaluate the effects of bladder volume on transabdominal ultrasound measurements of these parameters. Methods : Twenty-two patients undergoing transurethral resection of the prostate (TURP) were studied. Under general anesthesia just before TURP, a transrectal ultrasound measurement of prostate volume was obtained. The bladder was then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 6 publications
2
79
0
Order By: Relevance
“…Although transrectal ultrasound is considered more accurate, a number of studies demonstrate good correlation between the two methods and acceptable accuracy for the transabdominal route [16][17][18] . Moreover, the transabdominal ultrasound tends to overestimate the prostate volume in comparison with the transrectal technique, which indicates that the prostate volume of the studied population could be even smaller than the estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Although transrectal ultrasound is considered more accurate, a number of studies demonstrate good correlation between the two methods and acceptable accuracy for the transabdominal route [16][17][18] . Moreover, the transabdominal ultrasound tends to overestimate the prostate volume in comparison with the transrectal technique, which indicates that the prostate volume of the studied population could be even smaller than the estimated.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Obstruction at the bladder outlet depends on not just the size but, more so, the site of the adenoma. (3) Prostate adenoma causes distortion of the bladder neck and protrudes into the bladder lumen, which is seen as intravesical prostatic protrusion (IPP) on ultrasonography (10) (Fig. 1).…”
Section: Pathophysiology Of Bphmentioning
confidence: 99%
“…TRUS tends to be the most frequently used due to its availability and good size estimation [23]. DRE is a poor assessor of prostate size, making TRUS even more useful (18).…”
Section: Prostate Sizementioning
confidence: 99%
“…IPP grades are < 5mm, 5-10mm, or > 10mm respectively (22). Bladder volume at the time of measurement may significantly impact the measurement of IPP, thus studies have shown that a bladder volume of 100-200 mL is ideal (23). As the grade of IPP increases, so too will the severity of BOO.…”
Section: Intraprostatic Protrusionmentioning
confidence: 99%